Acceptability of a mobile smartphone application intervention to improve access to HIV prevention and care services for black men who have sex with men in the District of Columbia - Matthew E. Levy; Christopher Chauncey Watson; Leo Wilton; Vittoria Criss; Irene Kuo, Sara Nelson Glick; Sara Nelson Glick; Russell A. Brewer; Manya Magnus (Digital Culture & Education, 2015)
Eliminating racial HIV disparities among men who have sex with men (MSM) will require a greater uptake of HIV prevention and care interventions among Black MSM (BMSM), yet such strategies generally require meaningful engagement in a health care system that often does not meet the unique needs of BMSM. This study assessed the acceptability of, and correlates of having favorable perceptions of, a mobile smartphone application (app) intervention for BMSM that aims to remove structural barriers and improve access to culturally relevant HIV prevention and care services. An Internet-based sample of 93 BMSM completed an online survey on their perceptions of the app using 14 items measured on a 100-point visual analogue scale that were validated in exploratory factor analysis (alpha=0.95). Among the sample, perceptions of two sample app modules were generally favorable and most BMSM agreed that they would use the modules (81.2% and 87.1%). Correlates of having favorable perceptions included trusting medical advice from social networks, lacking private health insurance, and not having accessed a primary care physician in the last year. Our findings warrant the further development of this app and point to subgroups of BMSM for which it may have the greatest impact.